POLA DAN KESENJANGAN INTEGRASI PBL, STEAM, DAN METACOGNITIVE PROMPTS TERHADAP BERPIKIR KRITIS SISWA - Maharani, Novemia; Parno, Parno; Suwasono, Purbo; Hartatiek, Hartatiek (EduFisika: Jurnal Pendidikan Fisika, 2026)
This systematic literature review maps and synthesizes empirical evidence on Problem Based Learning (PBL), STEAM/STEM, and metacognitive prompts in relation to students’ critical thinking skills. Guided by the PRISMA 2020 framework, studies were retrieved from Scopus and screened through identification, screening, eligibility, and inclusion stages, resulting in 31 empirical articles published between 2021 and 2025. The findings show an increasing publication trend peaking in 2024, with secondary-school contexts and quasi-experimental designs predominating. PBL was the most frequently represented component (64.5%), followed by STEAM/STEM (41.9%) and metacognitive strategies (12.9%). Most studies reported positive contributions to critical thinking through distinct mechanisms: PBL through problem-solving, STEAM/STEM through interdisciplinary learning, and metacognitive strategies through regulation of thinking processes. However, none of the 31 studies simultaneously integrated PBL, STEAM/STEM, and metacognitive prompts with critical thinking within a coherent learning design. This finding reveals a clear empirical gap and supports the development and validation of an integrated PBL–STEAM model supported by metacognitive prompts, particularly for secondary science and physics education.